Multitherapeutic nanoplatform based on Scintillating Anthracene, Silver@Antracene, and Gold@Anthracene nanoparticles for combined radiation and photodynamic therapies: enhancing radiation dose while generating, trapping, probing, or delivering singlet oxygen species - Oliveira, Jeferson da Silva (2021)
We have synthesized anthracene and metal@anthracene core-shell nanoparticles and propose that they be used as a nanoplatform that combines radiation and photodynamic therapies. Synthesis of anthracene nanoparticles in the presence of colloidal silver or gold reduced the hydrodynamic radius in a concentration-dependent manner and caused core-shell nanostructures to grow, as revealed by AFM and DLS. Besides reduced size, the core-shell nanoparticles presented enhanced fluorescence emission. Fluorescence enhancements were higher for Ag@anthracene nanoparticles and for wavelengths approaching the plasmon resonance peak, which suggested a plasmon-enhancement phenomenon. The size-dependent enhancement in fluorescence associated with the distance between the metal core and the surface area of the nanoparticles provided an optimal core-shell diameter of 100150 nm. We investigated singlet oxygen (1O2) generation by electron spin resonance spectroscopy (ESR) with a spin-trap and by fluorescence spectroscopy. The ESR/spin-trap results revealed that, in the presence of a porphyrin, anthracene nanoparticles and the core-shell nanoparticles acted as energy mediators for 1O2 generation under exposure to light. Fluorescence suppression experiments showed that the core-shell nanoparticles captured 1O2 at higher rates because they presented smaller size and larger surface area than anthracene nanoparticles. Together, the ESR and fluorescence results suggested that overall production of 1O2 (1O2 captured by spin-trap + 1O2 captured by surface anthracene molecules) was higher for the core-shell nanoparticles than for anthracene nanoparticles. Moreover, because of plasmon-enhanced fluorescence and larger surface area, the Ag@anthracene nanoparticles stood out as a new and more sensitive fluorescent probe for 1O2. During irradiation with X-rays, both anthracene and Ag@anthracene nanoparticles trapped 1O2; subsequently, they afforded sustained release of the trapped 1O2 for up 12 days after irradiation. This could be an interesting strategy to extend the radiation therapy treatment after the irradiation sessions. Furthermore, the presence of the metallic nanoparticle in the core of the core-shell nanostructure increased interaction with X-rays, raising the radiation dose around the nanoparticle. Therefore, metal@anthracene nanostructures may allow cancer treatment by different approaches depending on nanoparticle configuration.